Isolation and characterization of a benzoylformate decarboxylase and a NAD+/NADP+-dependent benzaldehyde dehydrogenase involved in d-phenylglycine metabolism in Pseudomonas stutzeri ST-201 - Choedchai Saehuan (2018)
Following induction with d-phenylglycine both d-phenylglycine aminotransferase activity and benzoylformate decarboxylase activity were observed in cultures of Pseudomonas stutzeri ST-201. Induction with benzoylformate, on the other hand, induced only benzoylformate decarboxylase activity. Purification of the benzoylformate decarboxylase, followed by N-terminal sequencing, enabled the design of probes for hybridization with P. stutzeri ST-201 genomic DNA libraries. Sequencing of two overlapping genomic DNA restriction fragments revealed two open reading frames which were denoted dpgB and dpgC. Sequence alignments suggested that the genes encoded a thiamin-diphosphate-dependent decarboxylase and an aldehyde dehydrogenase, respectively. Both genes were isolated and expressed in Escherichia coli. The dpgB gene product was confirmed as a benzoylformate decarboxylase while the dpgC gene product was characterized as a NAD+/NADP+-dependent benzaldehyde dehydrogenase. In keeping with their high sequence identities (both greater than 85%) the kinetic properties of the two enzymes were similar to those of the homologous enzymes in the mandelate pathway of Pseudomonas putida ATCC 12633. However, Pseudomonas stutzeri ST-201 was unable to grow on either isomer of mandelate, and sequencing indicated that the dpgB gene did not form part of an operon. Thus it appears that the two enzymes form part of a d-phenylglycine, rather than mandelate, degrading pathway. © 2007 Elsevier B.V. All rights reserved.